Vaksin Kombinasi Newcastle Disease dengan Avian Influenza Memicu Imunitas Protektif pada Ayam Petelur terhadap Penyakit Tetelo dan Flu Burung (COMBINED NEWCASTLE DISEASE (ND) AND AVIAN INFLUENZA (AI) VACCINES INDUCE PROTECTIVE IMMUNE RESPONSE IN COMMERCIA - Kencana, Gusti Ayu Yuniati; Suartha, I Nyoman; Paramita, Ni Made Ayu Sintya; Handayani, Arini Nur (Jurnal Veteriner; Vol 17 No 2 (2016), 2016)
Newcastle disease (ND) and Avian Influenza (AI) are infectious diseases and still endemic in Indonesia.Prevention of the disease is conducted by vaccination of birds as the source of the infection. The use ofcombined ND-AI vaccine is expected to be able to prevent both diseases simultaneously. This study aimwas to determine the potency of combined ND-AI vaccine in field condition. Field trial vaccination wasconducted in commercial layer chickens in Tabanan Bali, and the HI test was conducted at the Faculty ofVeterinary Medicine Udayana University, Denpasar. Field trial in commercial layer chickens showed thatthe average HI titer of ND sera from pre-vaccinated chickens was 22.7HI units and AI titer was 21.27 HIunits. The ND titers increased to 25.47 HI Unit, 27.0 HI units, and to 28.73 HI units, whereas AI titersincreased to 27.93 HI Unit, 28.53 HI units, and 28.47 HI units in two, three and four weeks post-vaccinationwith the ND-AI combined vaccine, respectively. Statistically, based on ND and AI antibody pre and postvaccination,it is indicated that the combined ND-AI vaccine was able to induce immune response higherthan the protective titer level (>24). Period of collecting the sera samples also affected the titer of NDVand AI antibodies (P<0.01). Therefore it is recommended that vaccination should be conducted at antibodytiter of < 4 HI Unit.
Keywords: Vaccination, combined ND-AI vaccines, antibody titer ND and AI, HA/HI test, field test